The use of nested desirability functions and quality indices for multi-response robust parameter design problems. Issue Volume 29:Issues 4(2017) (2nd October 2017) - Bellucci, Joseph P.; Bauer, Kenneth W.
ABSTRACT: A multi-response robust parameter design (RPD) problem-solving technique based on desirability functions is presented in which the means and variances of all responses are placed on a level playing field. The proposal allows a decision maker to integrate their preferences for the individual means and variances. It is shown that the ensuing operating point is a system setting that produces a mutually robust set of responses. In addition, this article offers an approach to assess several RPD strategies via quality indices. The measures presented here allow for a more knowledgeable and comprehensive evaluation of the competing RPD strategies.